Voltage imaging using transgenic mouse lines expressing the GEVI ArcLight in two olfactory cell types - Jelena Platisa; Hongkui Zeng; Linda Madisen; 래리코헨; Vincent A Pieribone; Douglas A. Storace (Cold Spring Harbor Laboratory, 2022)
Genetically encoded voltage indicators (GEVIs) allow for cell-specific optical recordings of membrane potential changes in defined cell populations. One tool that would further their use in the in vivo mammalian brain is transgenic reporter animals that facilitate precise and repeatable targeting with high expression levels. The present literature on the development and use of transgenic mouse lines as vehicles for GEVI expression is limited. Here we report the first in vivo experiments using a transgenic reporter mouse for the GEVI ArcLight (Ai86(TITL-ArcLight)), which utilizes a Cre/tTA dependent expression system (TIGRE 1.0). Following pairing to appropriate Cre- and tTA transgenic mice, we report two mouse lines with ArcLight expression restricted to olfactory sensory neurons (OMP-ArcLight), and a subpopulation of interneurons that include periglomerular and granule cells (Emx1-ArcLight) in the olfactory bulb (OB). The ArcLight expression in these lines was sufficient for in vivo imaging of odorant responses in single trials. Odor responses were measured in the OB using epifluorescence and 2-photon imaging. The voltage responses were odor-specific and concentration-dependent, and confirmed earlier conclusions from calcium measurements. This study shows that the ArcLight Ai86(TITL-ArcLight) transgenic line is a flexible genetic tool that can be used to record neuronal electrical activity of a variety of cell types with a signal-to-noise ratio that is comparable to previous reports using viral transduction.